2020
DOI: 10.1177/1744806920908092
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal neuralgia causes neurodegeneration in rats associated with upregulation of the CD95/CD95L pathway

Abstract: Objectives: To explore the effects of trigeminal neuralgia on neurodegeneration in rats and the underlining mechanism. Methods: Sixty adult male Sprague Dawley rats were divided randomly into Chronic Constriction Injury of the Rat's Infraorbital Nerve (ION-CCI) group and sham group (n ¼ 30). Right suborbital nerve was ligated in ION-CCI group to establish a trigeminal neuralgia model. In sham group, suborbital nerve was exposed without ligation. Pain thresholds were measured before surgery and 1, 7, 15, and 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Growing evidence reveals that chronic neuroinflammation induced by activated glia contributes to neuronal injury (Jiang, Gong, Ge, et al, 2020; Zong et al, 2020). The Nissl body, a basophilic granule locating in neuron bodies or dendrites, can represent the changes of morphological structure and neuronal function (Wang, Long, et al, 2020). MAP2 staining could be found in dendrites and perikarya, which the intensity of MAP2 reflects the integrity of neurons (Biranowska et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence reveals that chronic neuroinflammation induced by activated glia contributes to neuronal injury (Jiang, Gong, Ge, et al, 2020; Zong et al, 2020). The Nissl body, a basophilic granule locating in neuron bodies or dendrites, can represent the changes of morphological structure and neuronal function (Wang, Long, et al, 2020). MAP2 staining could be found in dendrites and perikarya, which the intensity of MAP2 reflects the integrity of neurons (Biranowska et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study we observed that the levels of Angiopoietin-2, bFGF, HGF, SCF, TGF-α, and VEGF were significantly lower in the saliva of patients with TN in comparison with the control group. Studies have shown that low levels of VEGF play a role in neuronal degeneration which is a characteristic feature of trigeminal neuralgia [ 25 ]. Similarly, angiopoietin- 2 also promotes neovascularization along with VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…The enhanced activity of dopamine neurons is due to neural pathways connecting the spinal trigeminal subnucleus caudalis, the ventral tegmental region and the lateral parabrachial nucleus. In a rodent study, it was found that TN can cause neurodegeneration by upregulating the expression of CD95/CD95L, resulting in increased neuroinflammation and neuronal death [57].…”
Section: Trigeminal Neuralgia Related Studies In Rodentsmentioning
confidence: 99%